Study of the growth of CeO2 nanoparticles onto titanate nanotubes. (December 2015) - Marques, Thalles M.F.; Ferreira, Odair P.; da Costa, Jose A.P.; Fujisawa, Kazunori; Terrones, Mauricio; Viana, Bartolomeu C.
Abstract: We report the study of the growth of CeO2 nanoparticles on the external walls and Ce 4+ intercalation within the titanate nanotubes. The materials were fully characterized by multiple techniques, such as: Raman spectroscopy, infrared spectroscopy (FTIR), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM). The ion exchange processes in the titanate nanotubes were carried out using different concentrations of Ce 4+ in aqueous solution. Our results indicate that the growth of CeO2 nanoparticles grown mediated by the hydrolysis in the colloidal species of Ce and the attachment onto the titanate nanotubes happened and get it strongly anchored to the titanate nanotube surface by a simple electrostatic interaction between the nanoparticles and titanate nanotubes, which can explain the small size and even distribution of nanoparticles on titanate supports. It was demonstrated that it is possible to control the amount and size of CeO2 nanoparticles onto the nanotube surface, the species of the Ce ions intercalated between the layers of titanate nanotubes, and the materials could be tuned for using in specific catalysis in according with the amount of CeO2 nanoparticles, their oxygen vacancies/defects and the types of Ce species (Ce 4+ or Ce 3+ ) present into the nanotubes. Graphical abstract: Highlights: We have presented the mechanism of CeO2 nanoparticles growth and attachment onto titanate nanotubes surface. It takes place via hydrolysis reaction into the aqueous solutions and the attachment of the nanoparticles through the strong electrostatic interaction with nanotube surface. It allows, CeO2 nanoparticles with a narrow size distribution on the surface of the TiNT, avoiding the ripening and agglomeration of the CeO2 nanoparticles. This work can elucidate the mechanism of CeO2 nanoparticles growth with a even distribution onto the nanotube surface.